Theoretical Explanatory Model of International Adoption Failure: Attachment and Ecological Systems Perspectives. Issue 3 (2nd July 2016) - Verbovaya, Olga
ABSTRACT: International adoption, the transfer of children for parenting purposes from one nation to another, presents an extreme form of what is often known as "stranger" adoption, in contrast to relative adoption (Bartholet, 2005, p. 8). Adoption brings major changes to the lives of children and adoptive parents. Intercountry adoptions are associated with high monetary costs, long waiting periods to adopt, changes of the family environment, and cultural challenges, along with other bureaucratic and socioeconomic factors. This paper explores the issue of international adoption failure through the prism of two theories: attachment theory and ecological systems theory. The author begins with a brief history of international adoption into the United States, followed by a discussion of factors contributing into adoption failure as discussed in other literature. Next, adoption failure is theoretically analyzed using the concepts of attachment and ecological systems theories. Suggestions for adoption practitioners are included.